Hsa-miR-557 Inhibits Osteosarcoma Growth Through Targeting KRAS - Qiao, Zhi; Li, Jinfeng; Kou, Hongwei; Chen, Xiangrong; Bao, Deming; Shang, Guowei; Chen, Songfeng; Ji, Yanhui; Cheng, Tian; Wang, Yisheng; Liu, Hongjian (Frontiers in Genetics, 2022)
Abstract Objective: Osteosarcoma is the most common malignancy in skeletal system, studies showed important role of miRNAs in tumorigenesis, indicating miRNAs as possible therapeutic molecules. This study found an abnormal has-miR-557 expression level in osteosarcoma and tried to explore the potential function and the mechanism. Methods: Differential expression genes of osteosarcoma were analyzed using GSE28423 from GEO database. Survival analysis of miRNAs were conducted by data from TARGET-OS. STRING and miRDIP were used to predict the target genes of hsa-miR-557, in which KRAS was then verified by dual luciferase reporter assay. Expression of genes were detected by qPCR, and the level of proteins was detected by western blot. Proliferation ability of cells were detected by CCK-8 and cell cycle analysis. Tumor formation in nude mice was used to detect the influence of osteosarcoma by hsa-miR-557 in vivo. Results: Analysis from GEO and TARGET database found 12 miRNAs, 7 down regulated (hsa-miR-140-3p, hsa-miR-564, hsa-miR-765, hsa-miR-1224-5p, hsa-miR-95, hsa-miR-940, hsa-miR-557) and 5 up regulated (hsa-miR-362-3p, hsa-miR-149, hsa-miR-96, hsa-miR-744, hsa-miR-769-5p), are significant related with osteosarcoma prognosis. CCK-8 analysis and cell cycle analysis found hsa-miR-557 could significantly inhibit proliferation of osteosarcoma cells. Tumor formation study in nude mice showed that tumor size and weight were inhibited by hsa-miR-557 mimic transfection. Further studies also proved hsa-miR-557 could target the 3’-UTR of KRAS and modulate phosphorylation of downstream proteins. Conclusion: This study showed hsa-miR-557 could inhibit osteosarcoma growth both in vivo and in vitro, by modulating KRAS expression.